Pengelolaan Sampah Wisata dengan MAIN 4M+TP2 Terhadap Penanggulangan Banjir di Desa Dokan - Eqlima Elfira; Bina Melvia Girsang; Nurbaiti (Yayasan Kajian Riset dan Pengembangan RADISI, 2022)
Dokan village is an area that is included in the tourist village of Karo traditional houses. Tourist waste is one of the problems that will cause natural disaster floods and reduce the charm of tourism in the area. The purpose of this service activity is to apply MAIN 4M+TP2 to the community by disposing of, storing, burying, sorting waste and reforestation by palting Moringa trees. The results of these activities provide benefits around 94,1% of the community feels the benefits for plantations and tourism areas that are the domicile of the local community. This is evidenced by the enthusiasm of the community in asking questions and utilizing their domicile area to be used as e-commerce tourism by increasing people’s skills in the use of compost bags and public awareness of waste. Waste that is managed properly will generate income for the community and have economic value.